Current advances and strategies towards fully automated sample preparation for regulated LC–MS/MS bioanalysis. (September 2014) - Zheng, Naiyu; Jiang, Hao; Zeng, Jianing
Robotic liquid handlers (RLHs) have been widely used in automated sample preparation for liquid chromatography–tandem mass spectrometry (LC–MS/MS) bioanalysis. Automated sample preparation for regulated bioanalysis offers significantly higher assay efficiency, better data quality and potential bioanalytical cost-savings. For RLHs that are used for regulated bioanalysis, there are additional requirements, including 21 CFR Part 11 compliance, software validation, system qualification, calibration verification and proper maintenance. This article reviews recent advances in automated sample preparation for regulated bioanalysis in the last 5 years. Specifically, it covers the following aspects: regulated bioanalysis requirements, recent advances in automation hardware and software development, sample extraction workflow simplification, strategies towards fully automated sample extraction, and best practices in automated sample preparation for regulated bioanalysis.